Review of Social and Organizational Issues in Health Information Technology - Kuziemsky, Craig E. (Healthc Inform Res, 2015)
OBJECTIVES: This paper reviews organizational and social issues (OSIs) in health information technology (HIT). METHODS: A review and synthesis of the literature on OSIs in HIT was conducted. RESULTS: Five overarching themes with respect to OSIs in HIT were identified and discussed: scope and frameworks for defining OSIs in HIT, context matters, process immaturity and complexity, trade-offs will happen and need to be discussed openly, and means of studying OSIs in HIT. CONCLUSIONS: There is a wide body of literature that provides insight into OSIs in HIT, even if many of the studies are not explicitly labelled as such. The two biggest research needs are more explicit and theoretical studies of OSI in HITs and more research on integrating micro and macro perspectives of HIT use in organizations.